HUBUNGAN SEDIMENTASI TERHADAP STRUKTUR KOMUNITAS MAKROZOOBENTOS DI MUARA SUNGAI DESA PINTU AIR KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Ira Mutiara Lumbangaol; Hesti Wahyuningsih; Rusdi Leidonald (AQUACOASTMARINE, 2018)
Community activity gives influence to ecosystem condition in river estuary area in Desa Pintu Air and potentially affect water quality, characteristic and sedimentation rate, and abundance of marine biota especially macrozoobenthos. The study was conducted from May to July 2017 at Pintu Air Village, Langkat Regency, North Sumatra Province. The study was conducted by purposive sampling. The result showed that sedimentation rate in Desa Pintu Air estuary Station I was 3491,98 gr/ m2/day, Station II was 389,10 gr/m2/day, Station III was 369,15 gr/m2/day, Station IV equal to 1576,14 gr/m2/day, and Station V was 5353,51 gr/m2/day. Abundance of macrozoobenthos in Station I was 18 ind/m2 Station II of 17 ind/m2, Station III was 13 ind/m2, Station IV was 22 ind/m2 and Station V was 7 ind/m2 . The value of Diversity Index (H ') Station I was 4,08 Station II was 4,65 Station III was 4,83 Station IV was 5,12 and Station V was 4,07. Dominance index (C) Station I was 1,01 Station II was 0,32 Station III was 0,47 Station IV was 0,49 and Station V was 0,77. The value of sedimentation correlation to macrozoobentos abundance was -0,509, sedimentation correlation value to macrozoobentos diversity was -0.822, and the value of sedimentation correlation to macrozoobentos dominance was 0.850.Keywords : Sedimentation, Macrozoobenthos, Estuary